Sulfur Fumigation Processing of Traditional Chinese Medicinal Herbs: Beneficial or Detrimental? - Kan, Winnie L.; Ma, Bin; Lin, Ge (Frontiers in Pharmacology, 2011)
Majority of TCM herbs need to undergo post-harvesting processing to convert raw material into the form readily used for prescription. In general, processing procedures are either according to China Pharmacopoeia or based on traditional methods. Recently sulphur fumigation is increasingly used to replace traditional sun-drying for its pesticidal and anti-bacterial properties in a cheap and convenient manner. However, to date information on effects of sulphur fumigation on herbal safety and efficacy are limited. This article addresses potential destructive effects of sulphur fumigation on herbal efficacy and safety through reviewing currently available information. Since recently increased numbers of studies have demonstrated that sulphur fumigation induced dramatic changes in chemical profiles of various sulphur fumigated-herbs, consequent alteration of efficacy and/or potential incidence of toxicity are suspected. Therefore comprehensive investigations on effects of sulphur fumigation on toxicity, chemical profiles, pharmacokinetics and bioactivities of TCM herbs are timely to provide scientific basis for standardization and regulation of this currently common but potentially harmful processing method.